Reduksi Total Suspended Solid dari Limbah Cair Tahu dengan Adsorban Sabut Kelapa Pada Batch System: Pendekatan Response Surface Method - M Anggi Pramana; Monik Kasman (Universitas Batanghari Jambi, 2019)
Tofu wastewater from the tofu industry includes the process of washing soybeans, the use of tools, washing the floor, and cooking as well as the solution of the remaining soaking soybean. Concentration of tofu wastewater pollutant in particular total suspended solid (TSS) exceeds the quality standard of wastewater that has been stipulated in the Minister of Environment Regulation no. 5 of 2014. In this study, tofu wastewater treatment is carried out by the adsorption process in the batch system. Adsorbent used is coconut fiber. Analysis of the influence of independent variables, namely adsorbent weight, stirring speed and contact time on TSS adsorption was carried out using the response surface method approach. Adsorption process can reduce TSS from tofu wastewater to the range of 52-370 mg/L. The independent variable that most influences the dependent variable based on statistical analysis is contact time. The optimum TSS adsorption conditions based on analysis using the Design Expert 11 Application were reached at 40 minutes contact time.